“Dosis de microorganismos eficientes (EM) en producción de rábano (Raphanus sativus L.), en época lluviosa en la parroquia Guasaganda” . - Cabrera Gómez, María Marisol (2023)
The current research work was done in Guasaganda parish, La Maná canton, Cotopaxi province where three planting seasons were carried out with the specific objectives. The agronomic response of radish crop (Raphanus sativus L.) was identified with the inoculation of solution of efficient microorganisms (EM) per dose at 5% (0.50 ml), 10% (100 ml), and 15% (150 ml) in the rainy season. The laboratory results were analyzed in macro and micro elements of the soil, before sowing and after each sowing period. The cost-benefit relationship of the established treatments was evaluated. A completely randomized block design (CRBD) was used with four treatments (T1 5%), (T2 10%), (T3 15%), and (T4 0%) and five repetitions for each treatment. The evaluated variables were height of plant in cm, equatorial and polar diameter of bulb in cm, and production in kilograms. The treatment that stood out in the three periods with plant height, bulb diameter, and production was with the application of solution EM with the dose of 5%; the application of the established doses with EM influenced the treated soils, the pH and MO values increased. Moreover, it is remarkable that the pH ranges in the treated soils that were obtained during the investigation are optimal for the cultivation of radish.